Takhrij and Syarah Hadith of Chemistry: The Power of Iron Compounds Believed Since the Prophet's Time - Maulitta, Sherenia; Masrur, Ali (International Journal on Orange Technologies, 2021)
The purpose of this study was to discuss the hadith of the Prophet concerning the power of iron. This research method is qualitative through takhrij approach and hadith syarah with chemical analysis. The results and discussion of this research is iron is famous for its strength since the time of the Prophet, to be used as a war equipment and evidenced by scientific reviews of the physical and chemical properties of iron. Not only that, iron also at this time has the benefit to be used as household appliances, construction equipment, to military transportation equipment. The conclusion of this study is takhrij and syarah hadith about the strength and usefulness of iron has been used since the time of the Prophet.